Selection Of The Most Favorite Mineral Water Among Students Using The Simple Additive Weighting (SAW) Method - Indra Willy Juliansya; Hendra Cipta (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Mineral water is a type of water that contains natural minerals or other dissolved substances that can provide taste and health benefits. However, the selection of the most favorite mineral water among students is still not accurate. This is what makes the Simple Additive Weighting (SAW) method as data processing as the selection of the most favourite mineral water and generates a ranking of the weight calculation of the mineral water selection. The SAW method is used to solve qualitative problems in the selection of mineral water, comparing one criterion to another in order to assess each brand of mineral water in the UINSU Tuntungan area and provide the results of the selection of the most favourite mineral water. This study used 100 student data, 5 brands of mineral water, and 6 criteria, namely price, taste, packaging, water quality, brand, and availability. After determining the weight value of each attribute using Simple Additive Weighting (SAW), each alternative is chosen using ranking. This technique facilitates decision-making and yields the optimum outcome. When it comes to selecting mineral water, the findings of this study offer the finest option.